Utilization of cull chicken in the production of skinless chicken longaniza - Manus, Emily Dell A.
The study was conducted to develop an acceptable chicken longaniza using cull chicken meat. Phase I dealt with the development of a formulation for cull chicken longaniza. In Phase IA, evaluation of the raw material was done through visual inspection and microbial analysis for establishment of specifications. In Phase IB, modifications on the formula obtained from TLRC was done in order to obtain a more acceptable product. This modified formulation was used in the determination of the CCM:fat ratio. The original CCM:fat ratios were 85:15, 80:20 and 75:25. From the results of the sensory evaluation, a new set of CCM fat ratios was considered, namely: 75:25, 70:30 and 65:35. It was determined that the formula using 65:35 ratio had the highest level of acceptability and was the most preferred product by the panelists. Phase II involved the standardization of the chicken longaniza formulation obtained from Phase I. The general acceptability of the product was like very much. % Water holding capacity, shrinkage and size measurements were done on the three batches for purposes of setting specifications. In Phase III, consumer acceptability and cost analysis were done on the chicken longaniza. In consumer acceptability test, the respondents liked the product very much. From the cost analysis, a 450 gram-pack of the chicken longaniza can be sold at the price of P 32.76. From the results of the study, utilization of cull chicken as the raw material for chicken longaniza is very feasible.